Sport Training Program Monitor Based Android in Petanque Sports: Validity and Reliability Instrument - Rivan Saghita Pratama; Soegiyanto KS; Setya Rahayu; Irwan Budiono; Hadi Hadi; Satria Yudi Gontara; Abdian Asgi Sukmana; Ali MD Nadzalan; Muhammad Fatchurrahman Bagus Saputra (International Conference on Science, Education, and Technology, 2022)
The problem in this study is that the validity and reliability of the Sports Training Program Monitor application test are not known. The population in this study were all petanque athletes jawa tengah province and petanque coaches who were licensed at least at the provincial level which had a total of 114. The sampling technique in this study was purposive sampling. The sample in this study amounted to 30 samples. A total of 30 questions were asked. The results of this study are the calculated r value with n = 30 is 0.349, of the 30 questions submitted to the respondents, totaling 30 coaches and athletes, there are 26 questions that have a validity value of more than 0.349 and 4 questions have a value of less than 0.349. The reliability value of this instrument is 0.923 > 0.349, which means that this instrument is reliable. The conclusion from the results of the validity and reliability tests, based on those data, this instrument can be used on the condition that only 26 questions can be submitted to be used as test instruments for the Android-based monitor program sport training application.